2016
DOI: 10.1016/j.juro.2016.02.2966
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Diagnosis of Bladder Outlet Obstruction in Patients with Lower Urinary Tract Symptoms Using Ultrasound Decorrelation Analysis

Abstract: It is possible to noninvasively diagnose bladder outlet obstruction using the ultrasound decorrelation technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…Transperineal ultrasound uroflowmetry with a radio frequency reflection measurement to evaluate BOO was compared with pressure flow studies, and demonstrated a high ROC-AUC of 0.96, and good sensitivity (88%) and specificity (95%). 25 The COSMIN score was fair for criterion validity. Based on the COSMIN scores from one study with a sample size of n=45, the level of evidence was graded as low to evaluate BOO using transperineal ultrasound uroflowmetry (see table 5 ).…”
Section: Resultsmentioning
confidence: 96%
“…Transperineal ultrasound uroflowmetry with a radio frequency reflection measurement to evaluate BOO was compared with pressure flow studies, and demonstrated a high ROC-AUC of 0.96, and good sensitivity (88%) and specificity (95%). 25 The COSMIN score was fair for criterion validity. Based on the COSMIN scores from one study with a sample size of n=45, the level of evidence was graded as low to evaluate BOO using transperineal ultrasound uroflowmetry (see table 5 ).…”
Section: Resultsmentioning
confidence: 96%
“…Our new phantoms would suitably address such need. They can particularly be used as calibration tools for existing urodynamic imaging methods that involve clinical ultrasound scanners …”
Section: Discussionmentioning
confidence: 99%
“…As such, our development of a BPH‐featured urethra phantom serves not only as a case demonstration of the application of our protocol, but also as an investigative tool that can provide insight into the hydrodynamic interactions in the urethra when BPH is present. Representative results will be shown using ultrasound imaging, which is well regarded to be suitable for urodynamic investigations …”
Section: Introductionmentioning
confidence: 99%
“…Among them is the ultrasound decorrelation, using flow Doppler to distinguish laminar (normal) from turbulent (obstructed) flow. 38…”
Section: Prostate Size Measurementmentioning
confidence: 99%
“…In addition to existing well known techniques, new imaging modalities may be emerging. Among them is the ultrasound decorrelation, using flow Doppler to distinguish laminar (normal) from turbulent (obstructed) flow …”
Section: Introductionmentioning
confidence: 99%